Facilitators and barriers for return to work among patients with post-COVID-19 condition: a qualitative interview study - Aleksandra Sulg; Aki Vuokko; Kirsi Kvarnström; Mikko Varonen; Antti Malmivaara; Jari Arokoski; Helena Liira (Scandinavian Journal of Primary Health Care, 2025)
Background Post COVID-19 condition (PCC) can have long-lasting adverse effects, including impacts on work ability. This study explores the facilitators and barriers in the return-to-work (RTW) process.Design and methods Conducted in spring 2023 at the Outpatient Clinic for Long-Term Effects of COVID-19, this qualitative study involved phone interviews with 32 patients with PCC, of whom 28 were included in the analysis, while four interviews served as pilots. A research doctor conducted semi-structured interviews covering work ability, RTW actions and rehabilitation experiences. The interviews were recorded, transcribed verbatim and analyzed using an inductive approach.Results Several factors influenced work ability and the RTW process. For individual-related factors, self-guided rehabilitation, stress management, a positive attitude and high motivation supported RTW. Severe symptoms like fatigue and cognitive impairment, along with negative thoughts about them and experience of stress, hindered progress. Work-related factors included supportive employers and flexible work arrangements, while negative attitudes, skepticism about PCC and inflexible workloads were barriers. Health care-related and social factors showed that adequate emotional support and comprehensive healthcare services facilitated rehabilitation, whereas poor support, limited services and insufficient PCC understanding were obstacles. Regarding social insurance, partial sick leave supported RTW, but unmet criteria for benefits posed a barrier.Conclusion PCC’s multifactorial nature, complicated by work ability challenges, requires a holistic approach considering individual, social and work-related factors. Effective support involves understanding patients’ experiences and fostering collaboration among healthcare providers, employers and the social security system to facilitate RTW, especially in prolonged cases.